Mnemonic method in Portuguese for headaches in emergency room - Silva Júnior, Hilton Mariano da; Cardoso, Larissa Volpini (Headache Medicine, 2022)
Background It is of crucial importance to quickly stratify the risk of patients with headaches in the emergency setting, and mnemonics can be used to remember the alarm criteria in those cases. Such mnemonics were written in English and Spanish, but none in Portuguese. Objective To present the first mnemonic method in Portuguese for alarm criteria in emergency headaches in order to facilitate their identification and diagnosis. Methods A search was made through different databases for a mnemonic method regarding alarm criteria in emergency headaches that was written in Portuguese. None were found. Thus, the emergency criteria were gathered and turned into a mnemonic in Portuguese. Results We present the mnemonic method “RISADA PEGA”. Conclusion We believe this tool can be very useful in teaching and clinical settings.